Effect of Manurial Treatments on Availability of Nitrogen in the Soil - PATHAK, AN (Journal of Soil and Water Conservation, 2022)
TAKING into consideration the well-known fact that Indian soils are poor in nitrogen while they usually have ample supply of potash and phosphorus, it is needless to emphasize that out of the three essential nutrients for crop production nitro-gen is the most important one for us. Total nitrogen of our soils varies from 0.03 to 0.08 per cent, while the figures lie between 0.10 and 0.25 per cent for continental soils. Indian soils with 0.04 per cent total nitrogen are considered as average while continental soils with even 0.1 per cent nitrogen are taken to be as infertile. This is due to high nitrifying power of temperate soils brought about by high temperature and solar radia-tion that the available nitrogen in our fertile soils is more or less of the same order as in the continental soils.